Effect of processing routes on the mechanical, thermal and morphological properties of PLA-based hybrid biocomposite - Kaiser, Mohammad Rejaul; Anuar, Hazleen; Samat, Noorasikin; Abdul Razak, Shamsul Bahri (Polymer Research Center of Iran, 2013)
Due to environmental awareness and depletion of petroleum oil, bioplastics and their composites are one of the most researchable topics throughout the world. Polymers that are produced from renewable sources are expected to be the best alternative to replace conventional polymers. The bottles neck of these bioplastics is its cost which limits its application in certain purposes. Bioplastics ﬁlled or reinforced with natural ﬁbers can reduce cost and improve properties, like stiffness, strength and toughness of biocomposites. Impact strength and fracture toughness are the main demerits of short ﬁber-ﬁlled biocomposite. On the other hand, when nanoclay, having a very high aspect ratio, is mixed with bioplastics it may signiﬁcantly affect the thermal and mechanical properties of the ﬁnal composites. A composite may also suffer dispersion inefﬁciency, which is considered the key factor to improve the properties. The aim of this paper was to hybridize nanoclay and short kenaf ﬁber in polylactic acid (PLA) by double extrusion method and followed by mechanical, thermal and morphological characterizations. Mechanical properties showed improvement with nanoclay, speciﬁcally the impact strength increased more than 50 % compared with unreinforced PLA. A double extruded composite showed 3–10 % better tensile and ﬂexural properties than the single extruded composite. Similarly, addition of nanoclay increased decomposition and melting temperatures (T m) from 198 to 225 C and 152 to 155 C, respectively. Crystallization temperature (Tc ), however, dropped with nanoclay from 116 to 106 C and storage modulus (E’) increased by about 1 GPa. These ﬁndings were also supported by scanning electron micrograph (SEM) and transmission electron micrograph (TEM) where in double extruded composite a better dispersion of nanoclay was observed. By employing X-ray diffraction (XRD) it was found that higher percentage of crystallinity was obtained while Fourier transform infrared (FTIR) displayed new bond formation. The presence of nanoclay enhanced thermal and mechanical properties of the hybrid composite.